Inhibition of the key enzyme of sialic acid biosynthesis by C6-Se modified N-acetylmannosamine analogs. Issue 6 (10th March 2016) - Nieto-Garcia, Olaia; Wratil, Paul R.; Nguyen, Long D.; Böhrsch, Verena; Hinderlich, Stephan; Reutter, Werner; Hackenberger, Christian P. R.
Abstract : Synthetically accessible C6-analogs of N -acetylmannosamine (ManNAc) were tested as potential inhibitors of the bifunctional UDP- N -acetylglucosamine-2-epimerase/ N -acetylmannosamine kinase (GNE/MNK), the key enzyme of sialic acid biosynthesis. Abstract : Synthetically accessible C6-analogs of N -acetylmannosamine (ManNAc) were tested as potential inhibitors of the bifunctional UDP- N -acetylglucosamine-2-epimerase/ N -acetylmannosamine kinase (GNE/MNK), the key enzyme of sialic acid biosynthesis. Enzymatic experiments revealed that the modification introduced at the C6 saccharide position strongly influences the inhibitory potency. A C6-ManNAc diselenide dimer showed the strongest kinase inhibition in the low μM range among all the substrates tested and successfully reduced cell surface sialylation in Jurkat cells.